Study of dependence between clay mineral distribution and shale volume in reservoir rocks using geostatistical and petrophysical methods - Abdideh, Mohammad (Geodesy and Cartography, 2015)
Identify and obtain a detailed understanding of shale and its clay minerals in three segments; exploration, drilling and reservoir in the oil industry are very important. The study of the formation clay minerals in terms of depth and layers of earth is done through X-ray tests on samples taken from the reservoir which in comparison with logging requires a lot more time and cost and also can't provide continuous results because continuous sampling from the whole well is not possible. NGS (Gamma-ray Spectrometry) log is used to identify formation clay minerals that is an indicator of three radioactive elements thorium, uranium and potassium and the amount of each of these elements and according to amount of each of these elements and their ratio gives a description of clay minerals of each zone. CGR log represents the sum of two elements Thorium and potassium that are present in the shale and uranium has no effect on it. The CGR log is usually used as a shale indicator and it is an essential tool for determining the Shale volume in well logging operation. In this study the relationship between shale volume shown by the CGR log and the type of formation clay mineral was investigated. A very clear relationship between the shale volume and formation clay minerals was observed. In intervals with low shale volume the amount of active clay minerals, especially montmorillonite was higher and in intervals with high shale volume, inactive clay minerals were more. In order to investigate the spatial relation between the logging data, frequency distribution and correlation between logging data was studied. By using logging data and identifying the type of clay minerals in each zone and also the spatial correlation between logging data a suitable program for drilling and exploitation of oil fields in different areas can be proposed.